2019
DOI: 10.5617/nordina.6212
|View full text |Cite
|
Sign up to set email alerts
|

Mellan det globala och lokala – förskollärarstudenters meningsskapande om undervisning för hållbarhet i förskolan

Abstract: In previous studies on teacher education, student teachers and sustainability education, it has been found that there is a great need for more knowledge in higher education within the pedagogical field. Moreover, further studies are needed focused on problematizing how preschool teacher students understand and manage education for sustainable development. Such teaching can go beyond an environmental/scientific discourse through the integration of multiple dimensions of sustainability. The present study address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
1
0
5
Order By: Relevance
“…We can also see how the global perspective provides a broadened perspective in relation to thematic work in a digital world. This is similar to a study by Ärlemalm-Hagsér and Larsson (in press), in which digital tools are highlighted as important for concretizing a global perspective through, for example, different species of fruit depending on temperature zones and access to water as well as acknowledging people’s diverse living conditions in relation to such factors.…”
Section: Discussionsupporting
confidence: 63%
“…We can also see how the global perspective provides a broadened perspective in relation to thematic work in a digital world. This is similar to a study by Ärlemalm-Hagsér and Larsson (in press), in which digital tools are highlighted as important for concretizing a global perspective through, for example, different species of fruit depending on temperature zones and access to water as well as acknowledging people’s diverse living conditions in relation to such factors.…”
Section: Discussionsupporting
confidence: 63%
“…Asplund et al Siraj-Blatchford et al, 2010;Ärlemalm-Hagsér & Larsson, 2019). Slutsatsen är att medan fragmenterade arbetssätt kan ge viktig kunskap om till exempel ekologi, demokrati eller teknik, skapar de en diskrepans i relation till det holistiska tillvägagångssätt UNESCO menar behövs för att stödja transformativ kapacitet hos elever och barn (Rieckmann, 2018, UNESCO, 2020.…”
Section: Mot En äMnesövergripande Undervisning För Agenda 2030unclassified
“…According to Boldermo (2019), the research on education for sustainability in early childhood has been closely related to issues surrounding the environmental dimension, with an emphasis on the need to educate children to be environmentally responsible and to live sustainable lives. Children's active participation and agency in everyday educational practices are frequently raised in such contexts (Borg & Samuelsson, 2022;Ärlemalm-Hagsér, 2013). Borg and Gericke (2021) found that preschool teachers initially viewed sustainability from an environmental perspective.…”
Section: Social Sustainability In Preschoolmentioning
confidence: 99%